Application of Bayesian statistics to estimate nitrous oxide emission factors of three nitrogen fertilisers on UK grasslands. (July 2019) - Cowan, N.; Levy, P.; Drewer, J.; Carswell, A.; Shaw, R.; Simmons, I.; Bache, C.; Marinheiro, J.; Brichet, J.; Sanchez-Rodriguez, A.R.; Cotton, J.; Hill, P.W.; et al.
Abstract: Trapezoidal integration by linear interpolation of data points is by far the most commonly used method of cumulative flux calculations of nitrous oxide (N2 O) in studies that use flux chambers; however, this method is incapable of providing accurate uncertainty estimates. A Bayesian approach was used to calculate N2 O emission factors (EFs) and their associated uncertainties from flux chamber measurements made after the application of nitrogen fertilisers, in the form of ammonium nitrate (AN), urea (Ur) and urea treated with Agrotain® urease inhibitor (UI) at four grassland sites in the UK. The comparison between the cumulative fluxes estimated using the Bayesian and linear interpolation methods were broadly similar (R 2 = 0.79); however, the Bayesian method was capable of providing realistic uncertainties when a limited number of data points is available. The study reports mean EF values (and 95% confidence intervals) of 0.60 ± 0.63, 0.29 ± 0.22 and 0.26 ± 0.17% of applied N emitted as N2 O for the AN, Ur and UI treatments, respectively. There was no significant difference between N2 O emissions from the Ur and UI treatments. In the case of the automatic chamber data collected at one site in this study, the data did not fit the log-normal model, implying that more complex models may be needed, particularly for measurement data with high temporal resolution. Highlights: Bayesian statistics provided realistic uncertainties in cumulative N2 O flux estimates after fertiliser application. No significant difference in emissions of N2 O were observed between urea fertiliser and urea treated with urease inhibitor. Emissions of N2 O after the application of ammonium nitrate fertilisers is shown to be significantly higher than those of urea based fertilisers.